2007
DOI: 10.1021/jo070408f
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(0)-Catalyzed, Copper(I)-Mediated Coupling of Boronic Acids with Cyclic Thioamides. Selective Carbon−Carbon Bond Formation for the Functionalization of Heterocycles

Abstract: The palladium-catalyzed cross-coupling of cyclic thioamides with arylboronic acids in the presence of stoichiometric amounts of a copper(I) cofactor is described. The desulfitative carbon-carbon cross-coupling protocol is performed under neutral conditions and can be applied to a range of heterocyclic structures with embedded thioamide fragments. Successful carbon-carbon cross-coupling is independent of the ring size, aromaticity/nonaromaticity, the presence of additional heteroatoms, or other functional group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(35 citation statements)
references
References 65 publications
3
32
0
Order By: Relevance
“…Dihydropyrimidinethione 4f was used for the Liebeskind–Srogl coupling reaction with a phenylboronic acid to convert to 2-aryl-1,6-dihydropyrimidine 9 [1820]. The reaction was performed following a literature procedure [21] and was catalyzed by Pd(PPh 3 ) 4 and copper(I) thiophene-2-carboxylate (CuTC) under microwave heating at 100 °C for 25 min to afford aryl-substituted dihydropyrimidine 9 in 76% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Dihydropyrimidinethione 4f was used for the Liebeskind–Srogl coupling reaction with a phenylboronic acid to convert to 2-aryl-1,6-dihydropyrimidine 9 [1820]. The reaction was performed following a literature procedure [21] and was catalyzed by Pd(PPh 3 ) 4 and copper(I) thiophene-2-carboxylate (CuTC) under microwave heating at 100 °C for 25 min to afford aryl-substituted dihydropyrimidine 9 in 76% yield.…”
Section: Resultsmentioning
confidence: 99%
“…NMR spectra were recorded on a Bruker AV 400 spectrometer (400.13 MHz) in CDCl 3 or DMSO d 6 . Mass spectra were obtained on a Thermo Scientific DFS instrument (Double Focusing Sector Mass Spectrometer, Thermo Electron Corporation) with the direct inlet of the sample (the temper ature of the ionization chamber was 220-270 °C, the ionization potential was 70 eV).…”
Section: Methodsmentioning
confidence: 99%
“…[99] According to the authors, the reaction is independent of ring size, aromaticity/nonaromaticity and the presence of additional heteroatoms or other functional groups in the starting thioamide. [100] Interestingly, it was demonstrated that although the catalytic Pd 0 /Cu I system resulted solely in carbon-carbon bond formation, the use of stoichiometric amounts of Cu II under an air atmosphere resulted in carbon-sulfur bond formation (Scheme 76). [98,99] It has been shown that both types of thioamide cross-couplings are orthogonal to the traditional base-catalysed Suzuki-Miyaura cross-coupling of aryl halides with boronic acids.…”
Section: Miscellaneousmentioning
confidence: 99%